Effect of moisture content on hygrothermal properties: Comparison between pith and hemp shiv composites and other construction materials. (18th July 2022) - Abbas, Mohamed Said; McGregor, Fionn; Fabbri, Antonin; Ferroukhi, Mohammed Yacine; Perlot, Céline
Highlights: The evolution of several hygrothermal properties with moisture was measured. Pith composites' properties present a particular sensitivity to moisture. The transport of liquid water plays a significant role in hygroscopic transfers. Wet/dry cup tests don't systematically follow sorption isotherms nor their average. In wet/dry cup tests, the moisture content variation with thickness is almost linear. Abstract: This paper deals with the experimental assessment of the influence of water content on thermal conductivity, thermal effusivity, heat capacity and vapor permeability of pith and hemp shiv composites. The results, which will be used to enrich modelling databases, show that all four properties increase their value with relative humidity, especially for pith composites, while remaining within adequate margins. They are compared to the results commonly measured for other porous construction materials, namely hemp concrete, wood, and rammed earth. This comparison allows to better understand the influence of the material morphology and nature on hygrothermal properties in presence of moisture. It has been noted that, in hygroscopic conditions, the specific heat cannot always be deduced from the specific heat of water and of the dry material due to the interactions between the adsorbed water and the material. On the other hand, the transport of liquid water has been observed to play a significant role in the hygroscopic transfers.